A low-gas-generating, long-cycle ternary cathode material and a preparation method thereof
By adding doped element M in the preparation process of ternary positive electrode material and using core-shell structure and large and small particles to coat it together, the ternary positive electrode material has many side reactions and gas-producing bulges during use. The problem of degradation in cycling performance at high voltages has achieved better gas production performance and cycling stability.
Patent Information
- Application Number
- CN202310074052.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-18
AI Technical Summary
During the use of existing ternary positive electrode materials, there are problems such as battery side reactions, gas bulge and rapid decline in circulation performance under high voltage.
By directly adding doped element M in the process of preparing the precursor of the positive electrode material, and using the technology of core-shell structure and large and small particles to combine the coating, the uniform coating effect is formed, and the distribution of doped elements in the material lattice is improved. uniformity.
It effectively improves the gas production performance of LiNixCoyMnzO2 ternary cathode material and the cycling stability performance at high voltages, and improves the material's performance.
Smart Images

Figure BDA0004065661100000181 
Figure BDA0004065661100000201 
Figure HDA0004065661110000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of lithium-ion battery materials and relates to a low-gas-generating, long-cycle ternary positive electrode material and a preparation method thereof. Background Art
[0002] Ternary positive electrode materials have a higher specific capacity and lower material cost compared to materials such as lithium cobalt oxide. They have gradually replaced some low-capacity and high-cost positive electrode materials that cannot be widely used. However, during the use of ternary positive electrode materials, there are also many problems that may cause battery failure, such as more battery side reactions, gas bulging, and a rapid decrease in cycle performance under high voltage.
[0003] In order to solve the above problems, the existing technology mainly adopts dry multi-element simultaneous doping and coating. This method has the following problems: the mixing uniformity and the internal doping and external adhesion stability of the material cannot reach the ideal state. The nano-level coating agent is easy to form self-agglomeration during the material mixing stage. The obtained ternary positive electrode materials are quite different. The coating elements cannot be firmly attached to the surface of the single crystal, and the occurrence of side reactions cannot be effectively blocked. They are easy to fall off, causing the battery made of the positive electrode material to fail quickly. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention directly adds the doping element M during the preparation of the positive electrode material precursor, which can improve the uniformity of the distribution of the doping element M inside the material lattice. The coating element material adopts a core-shell structure and a large particle and small particle combined coating technology. The coating element material with smaller particles fills the gaps in the coating element material with larger particles, forming a core-shell structure with large particles as the core and small particles as the shell, thereby achieving a uniform coating effect and giving full play to the coating barrier effect.
[0005] Specifically, one aspect of the present invention provides a method for preparing a ternary positive electrode material, the method comprising the following steps:
[0006] (1) Ni salt, Co salt, Mn salt and M element source are subjected to coprecipitation reaction in water under the action of NaOH and ammonia water to obtain Ni, a precursor of the ternary positive electrode material. x Co y Mn z M (1-x-y-z) (OH)2, wherein 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, and M is one or more doping elements selected from Zr, Ti, Mg, B and Ba;
[0007] (2) mixing the ternary cathode material precursor, Sr source and lithium salt, and performing a sintering process to obtain a sintered material;
[0008] (3) The surface of the first-fired material is first coated with a W source to obtain a material coated with a W source, and then coated with one or two selected from an Al source and a Ti source, and subjected to secondary sintering to obtain the ternary positive electrode material.
[0009] In one or more embodiments, the doping element M comprises Zr, and the source of the M element comprises a water-soluble Zr-containing compound, preferably one or two selected from Li2ZrF6 and Zr(HPO4)2·H2O.
[0010] In one or more embodiments, the chemical formula of the ternary cathode material precursor is Ni x Co y Mn z M (1-x-y-z) In (OH)2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98.
[0011] In one or more embodiments, the particle size D50 of the ternary cathode material precursor is 2-15 μm.
[0012] In one or more embodiments, the specific surface area of the ternary cathode material precursor is 5-15 cm 2 / g.
[0013] In one or more embodiments, the pH of the coprecipitation reaction is 9-12, the reaction temperature is 60-80° C., and the reaction time is 5-12 h.
[0014] In one or more embodiments, the Sr source includes one or both selected from SrCO3 and SrO.
[0015] In one or more embodiments, the molar ratio of the ternary cathode material precursor to the Sr element in the Sr source is 1:(0.0001-0.001).
[0016] In one or more embodiments, the lithium salt includes one or more selected from lithium carbonate, lithium hydroxide, and lithium hydroxide monohydrate.
[0017] In one or more embodiments, the molar ratio of the lithium element in the lithium salt to the molar ratio of the ternary positive electrode material precursor is (1.02-1.08):1.
[0018] In one or more embodiments, the ternary cathode material precursor, Sr source and lithium salt are mixed by dry mixing or ball milling.
[0019] In one or more embodiments, the primary sintering has a holding temperature of 750-980° C. and a holding time of 6-12 h.
[0020] In one or more embodiments, the method includes, after the primary sintering, pulverizing the primary sintered material to a D50 particle size of 2-14 μm.
[0021] In one or more embodiments, the W source includes a W2O3, WO2 and (NH4) 10 W 12 O 41 ~xH2O or more.
[0022] In one or more embodiments, the particle size of the W source is 100-200 nm.
[0023] In one or more embodiments, the molar ratio of the calcined material to the W element in the W source is 1:(0.001-0.01).
[0024] In one or more embodiments, the W source is coated on the surface of the calcined material by wet mixing; preferably, the wet mixing comprises: first preparing a W source suspension by mixing a W source, a surfactant, a dispersant and water, then mixing the calcined material and the suspension, filtering and drying, thereby coating the W source on the surface of the calcined material to obtain a W source-coated material; wherein the surfactant is preferably hexadecyltrimethylammonium bromide, the dispersant is preferably polyethylene glycol-10000, and in the suspension, the concentration of the W source is preferably 0.5-2 g / L, the concentration of the surfactant is preferably 1-2 g / L, and the concentration of the dispersant is preferably 0.5-1.5 g / L.
[0025] In one or more embodiments, the average density of W atoms on the surface of the material coated with the W source is 1-800 / cm 2 .
[0026] In one or more embodiments, the Al source includes one or more selected from the group consisting of Al2O3, Al(OH)3, AlO9P3, and AlPO4.
[0027] In one or more embodiments, the Al source has a particle size of 30-60 nm.
[0028] In one or more embodiments, when the coating element includes Al, the amount ratio of the coating W source material to the Al element in the Al source is 1:(0.001-0.01).
[0029] In one or more embodiments, the Ti source includes one or more selected from TiO, TiO2, and Ti2O3.
[0030] In one or more embodiments, the particle size of the Ti source is 30-60 nm.
[0031] In one or more embodiments, when the coating element includes Ti, the amount ratio of the coating W source material to the amount of Ti element in the Ti source is 1:(0.001-0.01).
[0032] In one or more embodiments, one or two selected from the Al source and the Ti source are coated on the surface of the coated W source material by dry mixing.
[0033] In one or more embodiments, the average density of Al atoms or Ti atoms on the surface of the material coated with one or both of the Al source and the Ti source is 100-3000 / cm 2 .
[0034] In one or more embodiments, the holding temperature of the secondary sintering is 300-700° C., and the holding time is 6-12 h.
[0035] The present invention also includes a ternary positive electrode material prepared by the method described in any embodiment of the text.
[0036] Another aspect of the present invention provides a ternary positive electrode material, wherein the ternary positive electrode material is Li doped with Sr and coated with W and one or two elements selected from Al and Ti. n Ni x Co y Mn z M (1-x-y-z) O2, wherein n is 1.02-1.08, 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, and M is one or more doping elements selected from Zr, Ti, Mg, B and Ba.
[0037] In one or more embodiments, the doping element M comprises Zr, and the source of the M element comprises a water-soluble Zr-containing compound, preferably one or two selected from Li2ZrF6 and Zr(HPO4)2·H2O.
[0038] In one or more embodiments, the doping element M is doped into a precursor of the ternary cathode material.
[0039] In one or more embodiments, the Li n Ni x Co y Mn z M (1-x-y-z) In O2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98.
[0040] In one or more embodiments, in the ternary cathode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Sr element is 1:(0.0001-0.001).
[0041] In one or more embodiments, in the ternary cathode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to W element is 1:(0.001-0.01).
[0042] In one or more embodiments, the average density of W atoms on the surface of the ternary cathode material is 1-800 / cm 2 .
[0043] In one or more embodiments, when the coating element includes Al, in the ternary cathode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Al element is 1:(0.001-0.01).
[0044] In one or more embodiments, when the coating element includes Ti, in the ternary cathode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Ti element is 1:(0.001-0.01).
[0045] In one or more embodiments, the average density of Al atoms or Ti atoms on the surface of the ternary cathode material is 100-3000 / cm 2 .
[0046] The ternary positive electrode material of the present invention can be prepared by the method described in any embodiment of the text.
[0047] Another aspect of the present invention provides a positive electrode plate, wherein the positive electrode plate contains the ternary positive electrode material described in any embodiment of the present invention.
[0048] Another aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in any embodiment of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a schematic diagram of the structure of a sintered material coated with a W source, an Al source and a Ti source in the present invention. Figure 1 In the figure, 1 is a sintered material, 2 is a W source, 3 is an Al source, and 4 is a Ti source.
[0050] Figure 2 This is a scanning electron microscope (SEM) image of the positive electrode material prepared in Example 1 of the present invention.
[0051] Figure 3 This is a SEM image of the positive electrode material prepared in Example 2 of the present invention.
[0052] Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 1 of the present invention.
[0053] Figure 5 The graph is a cycle capacity retention rate curve of a lithium secondary battery using the positive electrode materials prepared by Example 1, Example 2 and Comparative Example 1 of the present invention at 2.8-4.25V. DETAILED DESCRIPTION
[0054] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0055] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0056] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.
[0057] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0058] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.
[0059] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0060] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0061] The present invention uses a multi-path method to dope elements, forming a stable internal lattice structure of the ternary positive electrode material, increasing the cycle stability of the ternary positive electrode material under high voltage; using a multi-level element coating method, the electrolyte and the surface of the ternary positive electrode material are effectively blocked, reducing the occurrence of side reactions between the electrolyte and the material surface, and reducing gas production. The present invention can effectively improve LiNi x Co y Mn z The gas production performance and cycle stability under high voltage of O2 (0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z=1) ternary positive electrode materials improve the overall performance of the materials, making the ternary single crystal positive electrode materials have a wide range of applications.
[0062] Ternary cathode material precursor
[0063] The chemical formula of the ternary cathode material precursor of the present invention is Ni x Co y Mn z M (1-x-y-z) (OH)2, wherein 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, M is a doping element. In some embodiments, the chemical formula Ni x Co y Mn z M (1-x-y-z) In (OH)2, 0.9≤x+y+z<1, for example, x+y+z can be 0.92, 0.94, 0.96, 0.98. Chemical formula Ni x Co y Mn z M (1-x-y-z)In (OH)2, x can be 0.5, 0.6, 0.63, 0.65, 0.7, 0.8, 0.9, y can be 0.02, 0.04, 0.06, 0.08, 0.1, 0.2, and z can be 0.1, 0.2, 0.24, 0.26, 0.28, 0.3. In some embodiments, the chemical formula Ni x Co y Mn z M (1-x-y-z) In (OH)2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98.
[0064] The doping element M applicable to the present invention can be selected from one or more of Zr, Ti, Mg, B, Ba, etc. In some embodiments, the doping element M is Zr. The M element plays a role in stabilizing the material structure inside the positive electrode material.
[0065] In some embodiments, the chemical formula of the ternary cathode material precursor of the present invention is Ni x Co y Mn z Zr (1-x-y-z) (OH)2, where 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, for example, the chemical formula of the ternary cathode material precursor can be Ni 0.63 Co 0.06 Mn 0.26 Zr 0.05 (OH)2.
[0066] The particle size D50 of the ternary cathode material precursor of the present invention may be 2-10 microns, such as 4 microns, 4.5 microns, 5 microns, 6 microns, or 8 microns.
[0067] The specific surface area of the ternary cathode material precursor of the present invention can be 5-15cm 2 / g, for example 8cm 2 / g, 10cm 2 / g, 11cm 2 / g, 12cm 2 / g, 12.5cm 2 / g, 13cm 2 / g, 14cm 2 / g.
[0068] The present invention adds the M element during the precursor preparation process to ensure that the M element is evenly distributed inside the material, and the effect on stabilizing the structure is greater than the effect of adding the M element to the dry mixture after the precursor preparation is completed.
[0069] The ternary cathode material precursor of the present invention is prepared by the following method: Ni salt, Co salt, Mn salt and M element source are subjected to coprecipitation reaction in water under the action of NaOH and ammonia water to obtain the ternary cathode material precursor Ni x Co y Mn z M (1-x-y-z) (OH)2.
[0070] The Ni salt, Co salt and Mn salt suitable for the present invention may be water-soluble salts of Ni, Co and Mn, such as sulfates.
[0071] In the present invention, the M element source refers to a substance used to introduce the M element into the precursor. The M element source suitable for the present invention can be a water-soluble M-containing compound, including but not limited to a water-soluble Zr-containing compound, a water-soluble Ti-containing compound, a water-soluble Mg-containing compound, a water-soluble B-containing compound, a water-soluble Ba-containing compound, etc. Examples of water-soluble Zr-containing compounds include Li2ZrF6 and Zr(HPO4)2·H2O. Examples of water-soluble Ti-containing compounds include Li2TiF6.
[0072] The pH of the coprecipitation reaction system is preferably 9-12, such as 9.5, 10, 11, the reaction temperature is preferably 60-80°C, such as 65°C, 70°C, 75°C, and the reaction time can be 5-12h, such as 8h, 10h.
[0073] The dosage ratio of Ni salt, Co salt, Mn salt, M element source and NaOH can be determined according to the chemical formula of the ternary positive electrode material precursor.
[0074] In some embodiments, a mixed solution of nickel salt, cobalt salt, manganese salt, NaOH solution, ammonia water and M element source are mixed, the pH and temperature of the system are controlled, and a coprecipitation reaction is carried out, and then filtered, washed and dried to obtain a ternary positive electrode material precursor Ni x Co y Mn z M (1-x-y-z) (OH)2. In the present invention, unless otherwise specified, the solvent of the solution or suspension is water.
[0075] Ternary cathode materials
[0076] The ternary cathode material of the present invention is prepared by mixing the ternary cathode material precursor of the present invention with a Sr source and a lithium salt, sintering once, coating with a W source and one or two selected from an Al source and a Ti source, and then sintering twice. The ternary cathode material of the present invention is Li doped with Sr and coated with W and one or two selected from Al and Ti. n Ni x Co y Mnz M (1-x-y-z) O2, wherein n is 1.02-1.08, 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, and M is one or more doping elements selected from Zr, Ti, Mg, B and Ba. In some embodiments, Li n Ni x Co y Mn z M (1-x-y-z) In O2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98.
[0077] In the present invention, the Sr source refers to a substance used to dope the positive electrode material with the Sr element. The Sr source applicable to the present invention may be a compound containing Sr, including but not limited to SrCO3 and SrO.
[0078] In the present invention, the molar ratio of the ternary cathode material precursor to the Sr element in the Sr source may be 1:(0.0001-0.001), for example, 1:0.0002, 1:0.0004, 1:0.0005, 1:0.0006, 1:0.0008.
[0079] The lithium salt suitable for the present invention is conventional in the art, for example, it can be lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate.
[0080] In the present invention, the molar ratio of the lithium element in the lithium salt to the substance of the ternary cathode material precursor may be (1.02-1.08):1, for example, 1.04:1, 1.06:1.
[0081] In the present invention, the ternary cathode material precursor, Sr source and lithium salt can be mixed by dry mixing or ball milling. In the present invention, dry mixing refers to stirring and mixing without adding a solvent. During mixing, the dry mixing process can be first mixed at a speed of 200-1000rpm, such as 500rpm for 2-10min, such as 5min, and then mixed at a speed of 2000-5000rpm for 10-30min, such as 20min. The ball milling parameters can be a mass ratio of 1 ball to 2 balls of 5:1-10:1, a rotation speed of 500-800rpm, a forward rotation of 4-6min, such as 5min, a reverse rotation of 4-6min, such as 5min, and a ball milling time of 2-4h.
[0082] After the ternary cathode material precursor, Sr source and lithium salt are uniformly mixed, a primary sintering can be performed in air, oxygen or a mixture of air and oxygen. When a mixed gas is used, the volume fraction of oxygen can be 40%-95%. The insulation temperature during the primary sintering can be 750-980°C, such as 800°C, 850°C, 900°C, 950°C, and the insulation time can be 6-12h, such as 8h, 10h.
[0083] The sintered product of the ternary positive electrode material precursor, Sr source and lithium salt (hereinafter referred to as the sintered material) can be crushed to control the particle size D50 to be 2-10 microns, such as 4 microns, 4.5 microns, 5 microns, 6 microns, and 8 microns. The crushing can be carried out by using a roller mill + colloid mill.
[0084] In the present invention, the W source refers to a substance used to coat the surface of the positive electrode material with W elements. The W source suitable for the present invention can be a W-containing compound, including but not limited to W2O3, WO2, (NH4) 10 W 12 O 41 ~xH2O, etc. The particle size D50 of the W source is preferably 100-200 nm, for example 150 nm.
[0085] In the present invention, the molar ratio of the calcined material to the W element in the W source may be 1:(0.001-0.01), for example, 1:0.0015, 1:0.002, 1:0.003, 1:0.005.
[0086] Preferably, the calcined material and the W source are mixed by wet mixing, wherein the W source, a surfactant, a dispersant and water are first used to prepare a stable W source suspension, and then the calcined material and the suspension are mixed, filtered and dried to obtain a W source-coated material, thereby achieving the coating of the calcined material by the W source. The W atomic radius is relatively large, and the coating effect of the dry coating is not as uniform as the wet coating effect, so the wet coating method is preferably used.
[0087] The surfactant is preferably hexadecyltrimethylammonium bromide. The dispersant is preferably polyethylene glycol-10000. In the suspension, the concentration of the W source can be 0.5-2g / L, such as 0.6g / L, 0.8g / L, 1g / L; the concentration of the surfactant can be 1-2g / L; the concentration of the dispersant can be 0.5-1.5g / L, such as 0.6g / L, 0.8g / L, 1g / L. When preparing the suspension, it is preferred to first dissolve the surfactant and the dispersant in water, then add the W source, and stir at 100-400rpm for 8-16h, such as 12h. For example, it can be stirred at 100-200rpm, such as 150rpm for 2-6h, such as 4h, and then dispersed at 200-400rpm, such as 250rpm for 6-10h, such as 8h, so as to obtain a uniformly dispersed suspension. When mixing the calcined material and the suspension, the calcined material is preferably added to the suspension, stirred at 100-200 rpm, for example, 150 rpm, for 0.5-2 h, for example, 1.5 h, and then filtered and dried to complete the coating.
[0088] In the present invention, the average density of W atoms on the surface of the material coated with W source is preferably 1-800 / cm 2 , for example 10 / cm 2 , 50 pieces / cm 2 , 100 pieces / cm 2 , 200 pieces / cm 2 , 500 pieces / cm 2 In some embodiments, the average density of W atoms on the surface of the material coated with W source is 100-200 / cm 2 , for example 140-160 pieces / cm 2 .
[0089] In the present invention, the W source and one or more selected from the Al source and the Ti source can be coated on the surface of the positive electrode material simultaneously or distributedly, but it is preferred to first coat the W source on the surface of the positive electrode material, and then coat the one or more selected from the Al source and the Ti source on the surface of the positive electrode material, and preferably, the W source is coated by a wet coating method, and the Al source and the Ti source are coated by a dry mixing method.
[0090] In the present invention, the Al source refers to a substance used to coat the surface of the positive electrode material with Al elements. The Al source suitable for the present invention can be an Al-containing compound, including but not limited to Al2O3, Al(OH)3, AlO9P3, AlPO4, etc. The particle size D50 of the Al source is preferably 30-60nm, for example 45nm.
[0091] In the present invention, the molar ratio of the calcined material to the Al element in the Al source may be 1:(0.001-0.01), for example, 1:0.002, 1:0.003, 1:0.004, 1:0.005.
[0092] In the present invention, the Ti source refers to a substance used to coat the surface of the positive electrode material with Ti elements. The Ti source suitable for the present invention can be a Ti-containing compound, including but not limited to TiO, TiO2, Ti2O3, etc. The particle size D50 of the Ti source is preferably 30-60nm, for example 45nm.
[0093] In the present invention, the molar ratio of the calcined material to the Ti element in the Ti source may be 1:(0.001-0.01), for example, 1:0.002, 1:0.004, 1:0.005, 1:0.006.
[0094] In the present invention, of the Al source and the Ti source, only the Al source may be used for coating, or both the Al source and the Ti source may be used for coating. When both the Al source and the Ti source are used for coating, coating the Al source and coating the Ti source are preferably performed simultaneously.
[0095] In the present invention, the Al source and the Ti source can be coated by dry mixing. During coating, the Al source and the Ti source can be first mixed at a rotation speed of 200-1000 rpm, such as 500 rpm, for 2-10 min, such as 5 min, and then mixed at a rotation speed of 2000-5000 rpm, such as 3000 rpm, for 5-20 min, such as 10 min.
[0096] In the present invention, the average density of Al atoms or Ti atoms on the surface of the material coated with Al source or Ti source is preferably 100-3000 / cm 2 , for example 200 pieces / cm 2 , 500 pieces / cm 2 , 1000 pieces / cm 2 , 1500 pieces / cm 2 , 2000pcs / cm 2 In some embodiments, the average density of Al atoms or Ti atoms on the surface of the material coated with Al source or Ti source is 500-1500 / cm 2 , for example 800-1200 pcs / cm 2 .
[0097] After coating the surface of the primary sintered material with a W source and one or two selected from an Al source and a Ti source, secondary sintering is performed to obtain a ternary positive electrode material. The secondary sintering can be performed in air, oxygen, or a mixture of air and oxygen. When a mixed gas is used, the volume fraction of oxygen can be 40%-95%. The insulation temperature during the secondary sintering can be 300-700°C, such as 400°C, 500°C, 600°C, and the insulation time can be 6-12h, such as 8h, 10h.
[0098] In some embodiments, the method for preparing the ternary cathode material of the present invention comprises the following steps:
[0099] (a) The ternary cathode material precursor Ni is mixed by dry mixing. x Co y Mn z M (1-x-y-z) (OH)2, lithium salt and Sr source are uniformly mixed, sintered once, and crushed to obtain a sintered material;
[0100] (b) preparing a W source into a uniformly dispersed suspension, adding the crushed calcined material to the suspension, stirring evenly to make the W source evenly coated on the surface of the calcined material, filtering and drying to obtain a coated material A;
[0101] (c) coating the coating material A with one or two selected from the Al source and the Ti source by dry mixing to obtain the coating material B;
[0102] (d) The coated material B is subjected to secondary sintering to obtain a ternary positive electrode material.
[0103] Lithium-ion battery
[0104] The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet of the lithium-ion battery of the present invention comprises the ternary positive electrode material of the present invention. The positive electrode sheet, the negative electrode sheet and the separator are laminated (for example, in a Z-shaped laminate or a winding laminate) according to the design requirements, and then the electrolyte is injected, and the lithium-ion battery is manufactured after aging, exhausting and heat sealing.
[0105] The positive electrode sheet includes a positive electrode collector and a positive electrode material layer formed on the surface of the positive electrode collector. The positive electrode material layer includes a positive electrode material, a conductive agent and a binder. The positive electrode material layer is obtained by coating a positive electrode slurry containing a positive electrode material, a conductive agent, a binder and a solvent on the positive electrode collector, and then rolling, die-cutting and drying. The solvent of the positive electrode slurry can be N-methyl-2-pyrrolidone (NMP). The positive electrode collector can be copper foil, aluminum foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode material includes one or more selected from lithium iron phosphate, binary positive electrode material, ternary positive electrode material, quaternary positive electrode material, etc. Preferably, the positive electrode material is a ternary positive electrode material of the present invention. The conductive agent of the positive electrode can be one or more selected from conductive carbon black, carbon fiber, acetylene black, conductive graphite, graphene, carbon nanotubes and carbon microspheres. The binder of the positive electrode can be one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene, polyvinyl alcohol, polyolefin, styrene-butadiene rubber, fluorinated rubber, polyurethane and sodium alginate. In some embodiments, the conductive agent in the positive electrode material layer is carbon black and carbon nanotubes, and the binder is PVDF. The content ratio of each component in the positive electrode material layer can be conventional, for example, the mass fraction of the positive electrode material can be 90%-98%, such as 92%, 94%, 96%, 97%, the mass fraction of the conductive agent can be 1%-5%, such as 1.5%, 2%, 3%, 3.5%, 4%, and the mass fraction of the binder can be 1%-5%, such as 1.5%, 2%, 2.5%, 3%, 4%.
[0106] The negative electrode sheet includes a negative electrode collector and a negative electrode material layer arranged on the surface of the negative electrode collector. The negative electrode collector can be a copper foil. The negative electrode material layer includes a negative electrode material, a conductive agent and a binder. The negative electrode material layer is obtained by coating a negative electrode slurry containing a negative electrode material, a conductive agent, a binder and a solvent onto the negative electrode collector, and then rolling, die cutting and drying. The solvent of the negative electrode slurry can be water. The negative electrode material can be selected from carbon powder, graphite, lithium metal, mesophase carbon balls, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, spinel structured lithiated TiO2-Li4Ti5O 12The negative electrode material layer and the negative electrode slurry may further include a thickener, such as carboxymethyl cellulose (CMC). In some embodiments, the negative electrode material in the negative electrode material layer is carbon powder, the conductive agent is conductive carbon black, the binder is styrene butadiene rubber, and the thickener is carboxymethyl cellulose. The mass ratio of each component in the negative electrode material layer can be conventional. For example, the mass fraction of the negative electrode material can be 90%-98%, for example 93%, 95%, 96%, 97%, the mass fraction of the conductive agent can be 0.5%-5%, for example 1%, 1.5%, 2%, the mass fraction of the binder can be 0.5%-5%, for example 1%, 1.5%, 2%, 2.5%, 3%, and the mass fraction of the thickener can be 0-5%, for example 1%, 1.5%, 1.8%, 2%, 3%.
[0107] The diaphragm can be a polymer diaphragm, a ceramic diaphragm or a polymer / ceramic composite diaphragm. The polymer diaphragm includes a single-layer polymer diaphragm and a multi-layer polymer diaphragm. The single-layer polymer diaphragm includes a polyethylene (PE) diaphragm and a polypropylene (PP) diaphragm. The composite polymer diaphragm includes a polyethylene and polystyrene mixed diaphragm.
[0108] The electrolyte can be a non-aqueous electrolyte, comprising an organic solvent and a lithium salt. The organic solvent can be a carbonate solvent commonly used in the art for electrolytes, including but not limited to one or more selected from ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, γ-butyrolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), preferably two or more. Preferably, the carbonate solvent comprises at least one cyclic carbonate and at least one chain carbonate. Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, butylene carbonate and γ-butyrolactone. Examples of chain carbonates include dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate. The volume ratio of cyclic carbonate and chain carbonate can be 1:4 to 2:3, such as 2:7, 1:3, 3:7, 1:2. The lithium salt may be a lithium salt commonly used in the art, including but not limited to lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(oxalate borate) (LiBOB), lithium acetate, lithium trifluoroacetate, lithium fluoroalkyl phosphate, lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium perchlorate, lithium hexafluoroarsenate, lithium fluoride, etc. In some embodiments, the lithium salt is LiPF6. The concentration of the lithium salt in the electrolyte may be 0.5-2 mol / L, for example 1 mol / L, 1.5 mol / L.
[0109] The present invention has the following beneficial effects:
[0110] 1. Part of the doping element M of the ternary cathode material is directly added when preparing the ternary cathode material precursor. The doping element M is more evenly distributed in the material, playing a better role in synergistically stabilizing the material structure;
[0111] 2. The dopant Sr source is added during the material mixing before the primary sintering, which can reduce the reaction temperature of the material sintering, achieve full reaction of the material, facilitate the formation of the lattice structure, obtain a solid layered ternary positive electrode material, reduce the lattice collapse during the material reaction, improve the lithium ion transmission channel, reduce the inherent internal resistance of the material, and improve the long-term cycle performance of the material under high voltage;
[0112] 3. The W source with a relatively large atomic radius is coated on the surface of the sintered material in the form of a suspension, which improves the uniformity of the coating material and the coating effect;
[0113] 4. If Figure 1 As shown in the figure, the Al source and Ti source with smaller atomic radius are coated in the outermost layer by dry coating, which not only fills the gaps of the inner coating layer particles (W source), but also forms a secondary coating on the surface of the inner coating layer (W source surface), effectively blocking the side reaction of direct contact between the electrolyte and the material, and improving the gas production performance of the material;
[0114] 5. The strong inner material structure and the reduction of side reactions of the outer coating layer play a synergistic role between the inner and outer materials, improving the material's high voltage cycle performance and high temperature gas production performance;
[0115] 6. The preparation method of the present invention can also be applied to the preparation of ternary positive electrode materials with similar components, and has a wide range of applications;
[0116] 7. The doping element M plays a good role in stabilizing the material structure of the ternary positive electrode material and improving the material cycle performance. Therefore, in the present invention, the element M is preferably added in the precursor preparation, which improves the uniformity of the distribution of the doping element M in the precursor nucleation process, can ensure the uniform distribution in the material, is conducive to the uniformity of the internal stress of the material, and plays a better supporting role in the performance of the positive electrode material cycle performance;
[0117] 8. Sr source has the function of reducing the sintering reaction temperature. It is added during the mixing process of the precursor and lithium salt and evenly distributed on the surface of the material, which plays a good role in reducing the activation energy of the reaction. The addition of doping element Sr can effectively reduce the optimal sintering temperature of the material by 5-20°C, which is conducive to reducing the energy consumption per ton of product;
[0118] 9. The coating material adopts the method of using large-size and small-size materials at the same time. The small particles can effectively fill the gaps and surfaces of large particles to form a dense coating layer, reducing the side reactions between the electrolyte and the material;
[0119] 10. The W source has a good capacity enhancement effect. It has a certain activity relative to the Al source and the Ti source and is prone to side reactions with the battery system. Therefore, the present invention preferably first coats the W source in the innermost layer of the material, and then coats the Al source and the Ti source on the surface of the material and the W source, so as to avoid side reactions between the material and the W source surface and increase the product cycle stability.
[0120] 11. The coating material adopts the method of synergistic coating of water phase and solid phase to improve the coating uniformity of the coating material on the material surface.
[0121] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.
[0122] Example 1
[0123] This example prepares a ternary positive electrode material:
[0124] (1) The positive electrode material precursor was synthesized by a coprecipitation method: a mixed solution of 2 mol / L nickel sulfate, cobalt sulfate and manganese sulfate (the molar ratio of nickel, cobalt and manganese elements was 65:7:28, and the element valence was +2), 2 mol / L NaOH solution, 3 mol / L ammonia solution and 0.05 mol / L Li2ZrF6 solution were added to a reactor, the pH value of the solution system was controlled to be 9.5, and the water bath was heated to maintain 65°C; after reacting for 10 hours, the mixture was filtered, washed and vacuum dried to obtain a composition of (Ni 0.63 Co 0.06 Mn 0.26 Zr 0.05 The precursor of )(OH)2 has a particle size D50 of about 4.5 microns and a specific surface area of about 12.5 cm 2 / g.
[0125] (2) Weigh 500 g of the precursor of step (1), 238.9 g of lithium hydroxide monohydrate and 0.4212 g of Sr2CO3, pour them into a high-speed mixer, mix at a speed of 500 rpm for 5 min, then mix at a speed of 3000 rpm for 20 min, transfer them into a sagger, raise the temperature to 950°C in an oxygen atmosphere, keep it at this temperature for 12 h, and then cool it to room temperature.
[0126] (3) The burnt material obtained in step (2) is rolled using a double-roll mill and finely pulverized using a colloid mill to control the particle size D50 to 4.5 μm.
[0127] (4) Add 1.5 L of deionized water to a washing tank, then add 1.5 g of hexadecyltrimethylammonium bromide and 1.2 g of polyethylene glycol-10000, stir thoroughly, then add 1.26 g of W2O3 (particle size D50 = 150 nm), stir and disperse at 150 rpm for 4 h, and disperse at 250 rpm for 8 h to obtain a uniformly dispersed W2O3 suspension.
[0128] (5) Weigh 400 g of the finely pulverized calcined material of step (3) and add it to the evenly dispersed suspension of step (4) for a coating: stir at a stirring speed of 150 rpm for 1 h, then filter, dry, and sieve to obtain coated material A. The average density of W atoms coated on the surface of material A was 147 atoms / cm after testing and analysis. 2 .
[0129] (6) Weigh 350 g of the coated material A of step (5) and 0.99 g of Al2O3 (particle size D50 = 45 nm), pour them into a high-speed mixer, and perform secondary coating: mix at a speed of 500 rpm for 5 min, and then mix at a speed of 3000 rpm for 10 min to obtain coated material B. The average density of Al atoms coated on the surface of material B was tested and analyzed to be 1138 atoms / cm2 .
[0130] (7) The coated material B of step (6) is transferred into a sagger, and the temperature is raised to 450° C. in an oxygen atmosphere, kept at this temperature for 10 h, cooled to room temperature, crushed and sieved to obtain a finished ternary positive electrode material. The morphology of the ternary positive electrode material is as follows: Figure 2 shown.
[0131] Example 2
[0132] In this embodiment, a ternary positive electrode material is prepared according to the method of embodiment 1, except that: in step (6), in addition to adding 350g of the coating material A of step (5) and 0.99g of Al2O3 to the high-speed mixer, 0.876g of TiO2 (particle size D50 = 45nm) is also added for secondary coating. The average density of W, Al, and Ti atoms coated on the surface of the coating material is 153 / cm3 respectively after testing and analysis. 2 , 1185 pieces / cm 2 、874pcs / cm 2 The morphology of the final ternary cathode material is as follows Figure 3 shown.
[0133] Comparative Example 1
[0134] This comparative example prepares a ternary positive electrode material:
[0135] (1) The positive electrode material precursor was synthesized by a coprecipitation method: a mixed solution of 2 mol / L nickel sulfate, cobalt sulfate and manganese sulfate (the molar ratio of nickel, cobalt and manganese elements was 65:7:28, and the element valence was +2), 2 mol / L NaOH solution and 3 mol / L ammonia solution were added to a reactor, the pH value of the solution system was controlled to be 9.5, and the water bath was heated to maintain 65°C; after reacting for 10 hours, the mixture was filtered, washed and vacuum dried to obtain a composition of (Ni 0.65 Co 0.07 Mn 0.28 The precursor of )(OH)2 has a particle size D50 of about 4.5 microns and a specific surface area of about 12.5 cm 2 / g.
[0136] (2) Weigh 500 g of the precursor of step (1), 238.9 g of lithium hydroxide monohydrate, 1.35 g of zirconium oxide and 0.4212 g of Sr2CO3, pour them into a high-speed mixer, mix at a speed of 500 rpm for 5 min, then mix at a speed of 3000 rpm for 20 min, transfer them into a sagger, raise the temperature to 950°C in an oxygen atmosphere, keep it at this temperature for 12 h, and then cool it to room temperature.
[0137] (3) The burnt material obtained in step (2) is rolled using a double-roll mill and finely pulverized using a colloid mill to control the particle size D50 to 4.5 μm.
[0138] (4) 350 g of the finely pulverized calcined material of step (3), 0.99 g of Al2O3 (particle size D50 = 45 nm) and 0.876 g of TiO2 (particle size D50 = 45 nm) were weighed and poured into a high-speed mixer for coating: mixing at a speed of 500 rpm for 5 min and then mixing at a speed of 3000 rpm for 10 min to obtain coated material C.
[0139] (5) The coated material C of step (6) is transferred into a sagger, and the temperature is raised to 450° C. in an oxygen atmosphere, kept at this temperature for 10 h, cooled to room temperature, and crushed and sieved to obtain a finished ternary positive electrode material. The morphology of the ternary positive electrode material is as follows: Figure 4 shown.
[0140] Comparative Example 2
[0141] In this comparative example, a ternary positive electrode material was prepared according to the method of comparative example 1, except that in step (4), in addition to adding 350 g of the finely pulverized calcined material of step (3), 0.99 g of Al2O3 and 0.876 g of TiO2 to the high-speed mixer, 1.1 g of W2O3 (particle size D50 = 150 nm) was also added for secondary coating. The morphology of the finally obtained positive electrode material is as follows: Figure 3 shown.
[0142] The preparation and testing of the soft pack battery of Comparative Example 2 are exactly the same as those of Comparative Example 1. The battery performance is as follows: Figure 5 And as shown in Table 1.
[0143] In the present invention, the average density of atoms coated on the surface of the ternary cathode material is tested and calculated according to the following method:
[0144] (1) Specific surface area test of ternary cathode materials
[0145] Weigh 1g (1.93m 2 / g) (accurate to 0.0001g), weigh 5g of the sample (accurate to 0.0001g). Use 3H-2000BET specific surface area tester. Ensure that the airflow in the pipeline is unobstructed. During the measurement, ensure that the peak area of the sample is basically consistent with the peak area of the standard sample, open the main valve of the cylinder, and then slowly open the output valve of the pressure reducing valve, adjust the valve output pressure to 0.4MPa, put the heating furnace on the sample tube, connect the heating furnace to the instrument, adjust the temperature to 150℃, and the heating time to 30min. After the purge is completed, turn off the purge power and the main power, remove the heating furnace, re-weigh the mass, calculate the sample mass m at this time, and install the sample tube.
[0146] Check the air inlet and outlet flow meters at 60-100mL / min, the main detection signal at 0 to -600, the voltage at 11-13V, and the current at 90-110mA. Add liquid nitrogen to each liquid nitrogen cup to 2 / 3 of the cup depth, and place them on the cup holders respectively. Pour liquid nitrogen into the cold trap constant temperature cup to a depth of 2-5cm, and place it on the pull-out plate on the side of the instrument. Select the 3H-2000BET reference method specific surface area test system test. When you hear a "beep" sound, it means that the communication is normal. Click Save to set the file name and save location; enter the sample name, sample quantity and mass m and save (generally the first path is the standard sample). After clicking the fully automatic start, the instrument enters the analysis stage, the buzzer sounds, the test ends, and the specific surface area X (m 2 / g).
[0147] (2) Element content test of ternary positive electrode materials
[0148] Weigh 0.5g of sample (accurate to 0.0001g) into a Teflon beaker, add 4mL of hydrochloric acid, place on a constant temperature heating plate and digest at 200°C until the sample is completely dissolved, add a small amount of water to clean the cup wall, and then digest until almost dry, transfer all to a 100mL volumetric flask, and dilute to the mark with water. Use inductively coupled plasma atomic emission spectrometry / plasma emission spectrometer to test the content Y (g / g) of each element in the sample.
[0149] (3) Calculation of the average density of atoms coated on the surface of ternary cathode materials
[0150] The average density of atoms is calculated according to the following formula
[0151]
[0152] Where: ρ: average density of atoms coated on the surface of ternary materials (a / cm 2 );
[0153] Y: mass percentage of the coating element of the ternary material (%, g / g);
[0154] Z: the number of atoms of the element in the ternary material coating element molecule;
[0155] X: Specific surface area of ternary material (m 2 / g);
[0156] M: amount of element substance coated by the ternary material (g / mol).
[0157] Test Case
[0158] The ternary positive electrode materials of Example 1-2 and Comparative Example 1-2 were made into 3.2Ah soft-pack batteries according to the following lithium secondary battery manufacturing process, and the battery performance was tested according to the following test method. The results are as follows: Figure 5 And as shown in Table 1.
[0159] Lithium secondary battery manufacturing process:
[0160] (1) Preparation of positive electrode
[0161] 97 wt% of ternary positive electrode material, 1 wt% of carbon black as a conductive agent, 1.5 wt% of polyvinylidene fluoride (PVDF) as a binder, and 0.5 wt% of carbon nanotubes (CNT) for enhancing conductivity were added to N-methyl-2-pyrrolidone (NMP) as a solvent to prepare a positive electrode mixture slurry with a solid content of 68%. The positive electrode mixture slurry was then coated on a 20-micron thick aluminum film as a positive electrode collector to ensure that the coating surface density was 380 g / m on both sides. 2 The positive electrode is prepared by drying and rolling.
[0162] (2) Preparation of negative electrode
[0163] 95 wt% of carbon powder as negative electrode active material, 1.0 wt% of conductive carbon black super-p as conductive material, and 2.5 wt% of styrene-butadiene rubber (SBR) and 1.5 wt% of carboxymethyl cellulose (CMC) premixed as binders were added to NMP as solvent to prepare a negative electrode active material slurry with a solid content of 48%. The negative electrode active material slurry was then coated on a copper film with a thickness of 10 microns as a negative electrode collector to ensure that the coating surface density was 220 g / m on both sides. 2 The negative electrode is prepared by drying and rolling.
[0164] (3) Preparation of non-aqueous electrolyte
[0165] Lithium hexafluorophosphate (LiPF6) was added to a solvent consisting of ethylene carbonate and diethyl carbonate in a volume ratio of 30:70 to prepare a 1 M LiPF6 non-aqueous electrolyte.
[0166] (4) Preparation of lithium secondary batteries
[0167] A polyethylene and polypropylene mixed separator is placed between the positive electrode and the negative electrode, and a lithium secondary battery is made by winding, injecting non-aqueous electrolyte, aging, evacuating, and heat sealing.
[0168] Battery performance test method:
[0169] (1) Charge and discharge capacity and cycle characteristics
[0170] The prepared lithium secondary battery was charged at 4.25V and 0.2C at 25°C and constant current / constant voltage (CC / CV) conditions, and then discharged at 0.33C to 2.8V under constant current (CC) conditions, and the capacity was measured; the prepared lithium secondary battery was charged at 4.25V and 1.0C at 25°C, and discharged at 1.0C to 2.8V, and the cycle was repeated from 1 to 1500 cycles, and the relative capacity retention rate at the 1500th cycle relative to the first cycle was measured.
[0171] (2) Gas production volume growth rate
[0172] The lithium secondary battery was placed in 70°C heat transfer oil for 60 days. The volume of the battery on the first day and the 60th day was tested using a Forbes volume tester. The battery volume growth rate was obtained by dividing the battery volume difference by 3.2Ah.
[0173] Table 1: Performance of lithium secondary batteries corresponding to Examples 1-2 and Comparative Examples 1-2
[0174]
[0175] From the test results of Example 1 and Example 2, it can be seen that the use of coating agent TiO2 can improve the capacity, cycle capacity retention rate and gas production performance. From the test results of Comparative Example 1 and Comparative Example 2, it can be seen that the use of coating agent W2O3 can improve the capacity, cycle capacity retention rate and gas production performance. From the experimental results of Example 2 and Comparative Example 2, it can be seen that doping Zr in the preparation of the precursor and coating W2O3 in the form of a suspension can significantly improve the capacity, cycle capacity retention rate and gas production performance.
Claims
1. A method for preparing a ternary positive electrode material, characterized in that: The method comprises the following steps: (1) Ni salt, Co salt, Mn salt and M element source are subjected to coprecipitation reaction in water under the action of NaOH and ammonia water to obtain the ternary cathode material precursor Ni x Co y Mn z M (1-x-y-z) (OH)2, wherein 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, and M is one or more doping elements selected from Zr, Ti, Mg, B and Ba; (2) mixing the ternary cathode material precursor, Sr source and lithium salt, and performing a sintering process to obtain a sintered material; (3) first coating the surface of the first-sintered material with a W source to obtain a material coated with the W source, and then coating it with one or two selected from an Al source and a Ti source, and performing secondary sintering to obtain the ternary positive electrode material; The W source is coated on the surface of the calcined material by wet mixing; the particle size of the W source is 100-200nm; one or two selected from the Al source and the Ti source are coated on the surface of the material coated with the W source by dry mixing; the particle size of the Al source is 30-60nm; the particle size of the Ti source is 30-60nm.
2. The method according to claim 1, characterized in that The method has one or more of the following features: The doping element M includes Zr, and the M element source includes a water-soluble Zr-containing compound; The chemical formula of the ternary cathode material precursor is Ni x Co y Mn z M (1-x-y-z) In (OH)2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98; The particle size D50 of the ternary cathode material precursor is 2-10 μm; The specific surface area of the ternary cathode material precursor is 5-15 cm 2 / g; The pH of the coprecipitation reaction is 9-12, the reaction temperature is 60-80° C., and the reaction time is 5-12 hours.
3. The method according to claim 1, characterized in that The doping element M includes Zr, and the M element source includes one or two selected from Li2ZrF6 and Zr(HPO4)2•H2O.
4. The method according to claim 1, characterized in that The method has one or more of the following features: The Sr source includes one or two selected from SrCO3 and SrO; The molar ratio of the ternary cathode material precursor to the Sr element in the Sr source is 1:(0.0001-0.001); The lithium salt includes one or more selected from lithium carbonate and lithium hydroxide; The molar ratio of the lithium element in the lithium salt to the ternary cathode material precursor is (1.02-1.08):1; Mixing the ternary cathode material precursor, Sr source and lithium salt by dry mixing or ball milling; The primary sintering has a holding temperature of 750-980°C and a holding time of 6-12h; The method comprises the following steps: after the primary sintering, crushing the sintered material to a D50 particle size of 2-15 μm.
5. The method according to claim 1, characterized in that The method has one or more of the following features: The W source includes W2O3, WO2 and (NH4) 10 W 12 O 41 One or more of xH2O; The molar ratio of the calcined material to the W element in the W source is 1:(0.001-0.01); The wet mixing comprises: firstly preparing a W source suspension by mixing a W source, a surfactant, a dispersant and water, then mixing the calcined material and the suspension, filtering and drying, thereby coating the W source on the surface of the calcined material to obtain a W source coated material; The average density of W atoms on the surface of the material coated with W source is 1-800 / cm 2 .
6. The method according to claim 5, characterized in that The surfactant is hexadecyltrimethylammonium bromide.
7. The method according to claim 5, characterized in that The dispersant is polyethylene glycol-10000.
8. The method according to claim 5, characterized in that In the suspension, the concentration of the W source is 0.5-2 g / L.
9. The method according to claim 5, characterized in that In the suspension, the concentration of the surfactant is 1-2 g / L.
10. The method according to claim 5, characterized in that In the suspension, the concentration of the dispersant is 0.5-1.5 g / L.
11. The method according to claim 1, characterized in that The method has one or more of the following features: The Al source includes one or more selected from Al2O3, Al(OH)3, AlO9P3 and AlPO4; When the coating element includes Al, the amount ratio of the material coating the W source to the amount of the Al element in the Al source is 1:(0.001-0.01); The Ti source includes one or more selected from TiO, TiO2 and Ti2O3; When the coating element includes Ti, the molar ratio of the material coating the W source to the amount of the Ti element in the Ti source is 1:(0.001-0.01); The average density of Al atoms or Ti atoms on the surface of the material coated with one or both of the Al source and the Ti source is 100-3000 / cm 2 ; The insulation temperature of the secondary sintering is 300-700° C., and the insulation time is 6-12 hours.
12. A ternary positive electrode material prepared by the method of any one of claims 1 to 11, characterized in that: The ternary positive electrode material is Li doped with Sr and coated with W and one or two elements selected from Al and Ti. n Ni x Co y Mn z M (1-x-y-z) O2, wherein n is 1.02-1.08, 0.4≤x≤0.95, 0<y<0.4, 0<z<0.4, x+y+z<1, and M is one or more doping elements selected from Zr, Ti, Mg, B and Ba.
13. The ternary cathode material according to claim 12, characterized in that: The ternary cathode material has one or more of the following characteristics: The doping element M includes Zr, and the M element source includes a water-soluble Zr-containing compound; The doping element M is doped into the precursor of the ternary positive electrode material; The Li n Ni x Co y Mn z M (1-x-y-z) In O2, 0.6≤x≤0.7, 0<y<0.1, 0.2<z<0.3, x+y+z<0.98; In the ternary positive electrode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Sr is 1:(0.0001-0.001); In the ternary positive electrode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to W is 1:(0.001-0.01); The average density of W atoms on the surface of the ternary positive electrode material is 1-800 / cm 2 ; When the coating element includes Al, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Al is 1:(0.001-0.01); When the coating element includes Ti, in the ternary positive electrode material, Li n Ni x Co y Mn z M (1-x-y-z) The molar ratio of O2 to Ti element is 1:(0.001-0.01); The average density of Al atoms or Ti atoms on the surface of the ternary positive electrode material is 100-3000 / cm 2 .
14. The ternary cathode material according to claim 12, characterized in that: The doping element M includes Zr, and the M element source includes one or two selected from Li2ZrF6 and Zr(HPO4)2•H2O.
15. A positive electrode sheet, characterized in that: The positive electrode sheet contains the ternary positive electrode material according to any one of claims 12-14.
16. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet according to claim 15.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and manufacturing method therefor
CN111164806A
Preparation method of single-crystal high-voltage multi-component composite cathode material
CN112086628A
High-rate ternary positive electrode material as well as preparation method and application thereof
CN114335547A